Administration Strategies for the Student Care System Using Digital Technology in Schools under the Sakon Nakhon Secondary Primary Educational Service Area Office - Wichianlom, Sarawoot; Buacharoen, Parichat (Rajapark Journal, 2024)
This research aimed to 1) study the current and desired status and the needs of the administration of the student care system using digital technology in schools under Sakon Nakhon Secondary Educational Service Area Office, and 2) develop the administration strategies for the student care system using digital technology in schools under Sakon Nakhon Secondary Educational Service Area Office. The study was conducted using a mixed-methods design. The sample in the study included educational institution administrators, deputy directors of educational institutions, teachers in charge of the student care system, counselor teachers, and guidance teachers in schools under the Sakon Nakhon Secondary Educational Service Area Office, selected by a purposive sampling method. The research instruments were a questionnaire, a semi-structured interview, and a strategy evaluation form. Statistics used for data analysis were percentage, mean, standard deviation, and priority needs index modified. The research results were revealed as follows: 1. The current status and the desired status of the administration of the student care system using digital technology in schools under Sakon Nakhon Secondary Educational Service Area Office were overall at a moderate level and were overall at a high level, respectively. The utmost importance lies in the necessity for prevention and problem-solving. And 2) The administration strategies of the student care system using digital technology in schools under the Sakon Nakhon Secondary Educational Service Area Office comprised six major strategies, and the administration strategies had appropriateness and feasibility overall at the highest level.